Requirements prioritization for a new multicriteria decision software: an application based on the Fuzzy TOPSIS method - Ruotolo, Viviane (2024)
Prioritizing software requirements is an extremely important activity for Software Engineering. It is approached in the literature as a multi-criteria decision problem, based on expert judgments. To deal with the subjectivity of these judgments, this study proposes the use of the Fuzzy TOPSIS method and carries out an application to prioritize requirements for new decision-making support software. The requirements were evaluated by three researchers involved in the development project. The results highlighted the requirements related to the use of qualitative and qualitative criteria, and the possibility of assigning weights to the criteria, as priorities. Unlike previous approaches, the applied method makes it possible to evaluate the weights of decision makers using linguistic terms. The methodological procedures adopted can be replicated in future applications aimed at prioritizing requirements.